Mechanical performance of stone mastic asphalt incorporating steel fiber - N. E., Jasni; K. A., Masri; Putra Jaya, Ramadhansyah; A. K., Arshad; E., Shaffie; J., Ahmad; A. H., Norhidayah (2019)
Stone Mastic Asphalt (SMA) is a gap-graded hot mix asphalt that contains a large percentage of course aggregate and bitumen filler mastic. SMA is suffered from severe binder drain down due to the gap graded aggregates mixtures. Large difference between the sizes of aggregate tend to reduce tensile strength of the asphalt mixture. To overcome this, a type of fiber which is steel fiber is utilized to improve the tensile strength of SMA. Thus, the aim of this study is to increase the strength of SMA by utilizing steel fiber. To prepare SMA mixtures, specimens were compacted by applying 50 blows on each face using Marshall Compactor. Then, the modified specimens were tested to investigate the performance in terms of Los Angeles Abrasion Test, Marshall Stability Test, Resilient Modulus Test, and Dynamic Creep. From the results, it indicates that the addition of 0.3% fiber leads to better stability and stiffness while 0.5% fiber for resilient and enhanced modulus dynamic creep at 25°C and 0.4% fiber at 40°C. Thus, it can be concluded that the addition of steel fiber in the mixture significantly enhance the overall performance of SMA.